Globalization after the pandemic - Qin, Hui 1953- (The Chinese University of Hong Kong Press, 2021)
"In this work, Qin Hui offers a bracing examination of the impact of coronavirus pandemic on political institutions in both China and the West. Deliberating on the contradiction between "human rights" and "human survival," he contends that China has achieved success in imposing coercive lockdowns to control the virus, but it will be a challenge to prevent the normalization of emergency measures from worsening human right conditions. The West, in contrast, must learn how democracies can efficiently enter a state of emergency and put an end to these measures at the proper time"--Publisher's website
Keywords: COVID-19 Pandemic, 2020- / Political aspects; Human rights